A copy number variant overlapping the 3ʹUTR of PLP1 causes spastic paraplegia - Alghamdi, Malak; Alharbi, Essa; Aljarallah, Salman; Alghamdi, Ghaida; Balahmar, Reham M.; Jado, Nisserin; Hamed, Hebattalah; Jamjoom, Dima; Bashiri, Fahad A.; Almontashiri, Naif A. M. (Journal of human genetics, 2025)
Leukodystrophy presents a significant diagnostic challenge due to its varied clinical presentation and similarity to other myelin disorders, characterized by abnormalities in myelin and white matter. Hypomyelination disorders, including Pelizaeus-Merzbacher disease (PMD) and hereditary spastic paraplegias (SPG), are associated with variants in the proteolipid protein 1 ( PLP1 ) gene, leading to symptoms ranging from severe dysmyelination in infancy to delayed dysmyelination and axonal degeneration in adulthood. Family history was taken, and pedigree was constructed. Recruitment included seven males and females with spastic paraplegia and nine healthy relatives, who were clinically investigated, and tested with molecular genetic assays including whole exome sequencing (WES), whole genome sequencing (WGS), and PCR amplification with fragment analysis on gel electrophoresis to identify and confirm the genetic cause. Family history was consistent with hereditary condition marked by progressive spastic paraplegia in 10 family members. Males had early onset and progressive paraplegia, and neurodegenerative conditions, resulting in a decline in the neurocognitive functions. However, in some females, the symptoms manifested later in their 30s–40s, leading to neurodegenerative conditions and spastic paraplegias. A total of 16 family members were available for genetic testing and segregation studies. Initial clinical WES in four members was negative. Next, WGS identified a novel copy number variant (CNV) loss (75.5 kb) involving the 3’UTR of the PLP1 gene in three members (the mother, affected son, but not in the unaffected son). Segregation studies in all 16 family members confirmed the presence of the CNV in five additional affected individuals and an asymptomatic female, but not in the eight asymptomatic individuals. Our study reports a novel 3ʹUTR CNV in PLP1 in a large family with several individuals affected with SPG. This finding expands the mutational landscape of the PLP1 -related diseases to include CNV and, possibly, small sequence changes in the regulatory regions of PLP1 , that would otherwise be overlooked during the interpretation of the next generation sequencing data.